2019
DOI: 10.1515/eces-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Removal from Groundwater by Technological Process Optimization

Abstract: Fluoride removal from aqueous solutions was studied using nanofiltration and sorption techniques which have always been best key ways to deal with water contaminated by fluoride. In this presented work, we were firstly interested on fluoridated rejected water overcoming the drawback of RO membrane process of groundwater treatment plant in Baltic region (Kretinga, Lithuania). Opoka sorbent has shown effective results of fluoride sorption with efficiency higher than 77 %. In order to understand the sorption phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It was also confirmed that among the natural materials, opoka rock has the highest sorption capacity in water solutions. Opoka-based materials can also be used for the removal of other compounds, such as aluminum [46], catechol [51], fluoride [52], polypropylene [53] or cadmium [54], as well as gases (carbon dioxide (CO 2 ) and sulfur dioxide (SO 2 )) [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…It was also confirmed that among the natural materials, opoka rock has the highest sorption capacity in water solutions. Opoka-based materials can also be used for the removal of other compounds, such as aluminum [46], catechol [51], fluoride [52], polypropylene [53] or cadmium [54], as well as gases (carbon dioxide (CO 2 ) and sulfur dioxide (SO 2 )) [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Defluoridation poses a significant challenge in reducing fluoride concentration to meet acceptable standards set by the World Health Organization (WHO) for potable water, which is below 1.5 mg/L [ 5 ]. Numerous technologies have been utilized for the eradication of fluoride from water, encompassing adsorption [ 6 , 7 ], membrane separation [ 8 , 9 ], ion exchange [ 10 , 11 ], and precipitation–coagulation [ 12 ]. Within these technologies, membrane-based processes have garnered considerable interest in removing fluoride from water in recent times owing to their commendable efficiency and dependability.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is much research related to the process optimization of water treatment membrane technologies [10][11][12][13][14]. However, most of the aforementioned research is based on experimental approaches without mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%